Augmentation of full-thickness rotator cuff tears with a bioinductive collagen implant does not reduce retear rates: a propensity matched cohort study - Rab, Peter; Shirinskiy, Igor J.; Kimmeyer, Michael; Macken, Arno A.; Calamita, Andrea G.; Colombini, Antonio G.; Buijze, Geert Alexander; Lafosse, Thibault (BMC musculoskeletal disorders, 2025)
To compare the clinical and radiographic outcomes after full-thickness RC repair with and without performing augmentation with a bioinductive collagen implant (BCI).
Gesehen am 23.10.2025